LncRNA-Hh Strengthen Cancer Stem Cells Generation in Twist-Positive Breast Cancer via Activation of Hedgehog Signaling Pathway. (17th November 2015) - Zhou, Mingli; Hou, Yixuan; Yang, Guanglun; Zhang, Hailong; Tu, Gang; Du, Yan-e; Wen, Siyang; Xu, Liyun; Tang, Xi; Tang, Shifu; Yang, Li; Cui, Xiaojiang; et al.
Summary: Cancer stem cells (CSCs) are a subpopulation of neoplastic cells with self-renewal capacity and limitless proliferative potential as well as high invasion and migration capacity. These cells are commonly associated with epithelial-mesenchymal transition (EMT), which is also critical for tumor metastasis. Recent studies illustrate a direct link between EMT and stemness of cancer cells. Long non-coding RNAs (lncRNAs) have emerged as important new players in the regulation of multiple cellular processes in various diseases. To date, the role of lncRNAs in EMT-associated CSC stemness acquisition and maintenance remains unclear. In this study, we discovered that a set of lncRNAs were dysregulated in Twist-positive mammosphere cells using lncRNA microarray analysis. Multiple lncRNAs-associated canonical signaling pathways were identified via bioinformatics analysis. Especially, the Shh-GLI1 pathway associated lncRNA-Hh, transcriptionally regulated by Twist, directly targets GAS1 to stimulate the activation of hedgehog signaling (Hh). The activated Hh increases GLI1 expression, and enhances the expression of SOX2 and OCT4 to play a regulatory role in CSC maintenance. Thus, the mammosphere-formation efficiency (MFE) and the self-renewal capacity in vitro, and oncogenicity in vivo in Twist-positive breast cancer cells are elevated. lncRNA-Hh silence in Twist-positive breast cells attenuates the activated Shh-GLI1 signaling and decreases the CSC-associated SOX and OCT4 levels, thus reduces the MFE and tumorigenesis of transplanted tumor. Our results reveal that lncRNAs function as an important regulator endowing Twist-induced EMT cells to gain the CSC-like stemness properties.